2018
DOI: 10.1016/j.pepi.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamic turbulence and the geodynamo

Abstract: The ARES Directorate at JSC has researched the physical processes that create planetary magnetic fields through dynamo action since 2007. The "dynamo problem" has existed since 1600, when William Gilbert, physician to Queen Elizabeth I, recognized that the Earth was a giant magnet. In 1919, Joseph Larmor proposed that solar (and by implication, planetary) magnetism was due to magnetohydrodynamics (MHD), but full acceptance did not occur until Glatzmaier and Roberts solved the MHD equations numerically and simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(40 citation statements)
references
References 51 publications
3
37
0
Order By: Relevance
“…(Conduction in the mantle starts at r s = 5371 km and finishes at the CMB at r o = 3480 km; its effects are modeled as due to a spherical surface current of conductance σ c at r = r c .) With regard to the magnetic spectra due to magnetohydrodynamic (MHD) turbulence, consider Figure 2, where we use, as an example, the spectrum R o n (r 3 ) from Figure 1, and then scale and overlay on R o n (r 3 ) a turbulent spectrum from simulation NM06 in [26]. This simulation was of rotating, dissipative, forced MHD turbulence run on a 64 3 grid for a very long time; the kinetic and magnetic Reynolds numbers were 285 and 200, respectively; the wavenumber range was 1 ≤ k < 32; and the forcing wave number was k f = 9, which pushed the spectrum up for k∼k f .…”
Section: Power Spectrum Of the Geomagnetic Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…(Conduction in the mantle starts at r s = 5371 km and finishes at the CMB at r o = 3480 km; its effects are modeled as due to a spherical surface current of conductance σ c at r = r c .) With regard to the magnetic spectra due to magnetohydrodynamic (MHD) turbulence, consider Figure 2, where we use, as an example, the spectrum R o n (r 3 ) from Figure 1, and then scale and overlay on R o n (r 3 ) a turbulent spectrum from simulation NM06 in [26]. This simulation was of rotating, dissipative, forced MHD turbulence run on a 64 3 grid for a very long time; the kinetic and magnetic Reynolds numbers were 285 and 200, respectively; the wavenumber range was 1 ≤ k < 32; and the forcing wave number was k f = 9, which pushed the spectrum up for k∼k f .…”
Section: Power Spectrum Of the Geomagnetic Fieldmentioning
confidence: 99%
“…Figure 2 demonstrates that the presence of mantle electrical conductivity is needed to produce a magnetic spectrum on the CMB that is not flat and, at least at low-k, behaves as if it originated out of a turbulent outer core. 1 along with a scaled, overlaid turbulent spectrum from simulation NM06 discussed in [26]; NM06 was forced at wavenumber k f = 9 (please see text for more details). The Mauersberger-Lowes spectrum R n (r o ) on the CMB and a representative Kolmogorov spectrum k −5/3 are also shown.…”
Section: Power Spectrum Of the Geomagnetic Fieldmentioning
confidence: 99%
“…If the expressions for E and are placed into ( 6 ), it is straightforward to determine the partition function and from this the expectation values of the means and variances for the variables and . The means are expected to be zero, but in numerical simulations of both ideal and real MHD turbulence in a periodic box, it has been found that the dynamical time-averages of the magnetic field coefficients with the smallest wavenumber can be very large compared to their standard deviations [ 15 , 16 , 22 , 23 , 24 , 25 ]. This is an example of broken ergodicity [ 26 ].…”
Section: Statistical Mechanics Of Mhd Turbulencementioning
confidence: 99%
“…In periodic box models, this dipole moment vector tends to align itself with a rotation axis, if one is present in ideal MHD turbulence [ 22 ]. However, in dissipative, driven MHD turbulence, this alignment can be affected by the manner in which the system is forced [ 15 , 16 ]. If the angular rotation vector is in the z -direction, alignment in the spherical shell model occurs because the component becomes large dynamically, while the components become much smaller, i.e., we have broken symmetry.…”
Section: Statistical Mechanics Of Mhd Turbulencementioning
confidence: 99%
See 1 more Smart Citation